Pengaruh Customer Relationship Management dan Brand Image terhadap Kepuasan Pasien Rawat Jalan dengan Keputusan Berkunjung sebagai Variabel Intervening pada Instalasi Rawat Jalan Klinik Khadijah PKU Muhammadiyah Muncar - Indah Kurniawati; Ni Nyoman Putu Martini; Toni Herlambang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of Customer Relationship Management (CRM) and Brand Image on outpatient satisfaction, as well as their indirect influence on the decision to visit through patient satisfaction as an intervening variable at the Khadijah PKU Muhammadiyah Muncar Outpatient Clinic. The research method used was quantitative with an explanatory research approach, involving 100 outpatients as a sample through accidental sampling. Data analysis was performed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that CRM and Brand Image have a positive and significant influence on patient satisfaction, with CRM having a more dominant influence; meanwhile, the influence of CRM and Brand Image on the decision to visit occurs indirectly through patient satisfaction as a full intervening variable. In conclusion, improving the quality of CRM and Brand Image will increase patient satisfaction, which in turn encourages patients' decisions to revisit the clinic. Keywords: Customer Relationship Management, Brand Image, Patient Satisfaction